Detection of Cutaneous Leishmaniasis by PCR in Fasa district in 2012 - Mehdi Sharafi; Babak Pezeshki; Abdollah Reisi; Mohsen Kalantari; Mohammad Mehdi Naghizadeh; Soulmaz Dast Manesh (Fasa University of Medical Sciences, 2013)
Background & Objective: Leishmaniasis is a common disease between humans and animals caused by protozoa of the genus Leishmania spp. It is transmitted by the female species of Phlebotomus.The most common form of leishmaniasis is the cutaneous form seen as either dry (urban) or wet (Rural). Detection of cutaneous leishmaniasis species is not reliable by microscopy. Among the methods, PCR is useful for this purpose. In this study, we aimed to investigate the cutaneous leishmaniasis species by PCR method in Fasa district. Material & Methods: Slit biopsies were collected from 138 suspected cases of cutaneous leishmaniasis who were presented, consecutively, in Fasa district from April 2011 to February 2012. After the microscopy, the entire smear was then scraped off the slide surface for DNA extraction and PCR assay. Results: All 138 investigated smears were reported positive by microscopy and nested PCR assay. In PCR, One of the smears had the 750-bp band, indicative of L. tropica and the rest had the 560-bp band indicative of L. major. Conclusion: In conclusion, the cutaneous leishmaniasis found in Fasa district is predominantly Rural Cutaneous Leishmaniasis. The PCR-based assay used in the present study appears to be a suitable and powerful tool for the characterization of Leishmanial species.